Women on the Move: A Comparative Analysis of Salaf and Contemporary Ulama on Solo Female Travel in Islam - Shofwil Widad; Zainuddin Sunarto; Syamilah Muslimah Awaluddin (Al-Qalam Institute, 2026)
This study aims to examine the views of Salafi and contemporary scholars on the law of women traveling without a mahram in the context of modern travel. The background of this research highlights the tension between classical interpretations that prohibit women from traveling without a mahram and the growing demand for female participation in the global public sphere. The research employs a qualitative approach, using library research and normative and comparative methods to analyse classical and contemporary fiqh texts. The main findings reveal that the differing views between Salafi and contemporary scholars regarding women’s travel without a mahram stem from differences in identifying the ‘illah (legal cause) of the prohibition, with some scholars emphasizing physical protection, while others focus on social safety. While most Salafi scholars view the mahram as mandatory, contemporary scholars argue that modern security systems can replace the mahram’s role. This study contributes by offering a moderate legal synthesis that integrates maqashid al-Shariah with contemporary social realities. It recommends a paradigm shift in understanding the role of mahrams and the collective security system in supporting women’s mobility.